1991
DOI: 10.1002/hep.1840140124
|View full text |Cite
|
Sign up to set email alerts
|

Permanent engraftment and function of hepatocytes delivered to the liver: Implications for gene therapy and Liver Repopulation

Abstract: To examine the distribution of intrasplenically transplanted hepatocytes, we used HBsAg-producing G7 HBV transgenic hepatocytes or cells labeled with 111In. Most hepatocytes translocated to the liver (55% +/- 7%; mean +/- S.D.); the spleen retained a smaller fraction (15% +/- 3%); and some transplanted cells localized in lungs (3%) or pancreas (1%). Transplanted hepatocytes were rapidly assimilated into the liver lobule. Morphometrical quantitation indicated that the numbers of transplanted hepatocytes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
98
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 186 publications
(108 citation statements)
references
References 24 publications
8
98
0
2
Order By: Relevance
“…70,72,73 These studies also showed that: (i) transplantation of normal hepatocytes as few as 1% of the patient liver mass could lead to metabolic benefits; 73 (ii) hepatocyte transplantation was safe in babies, therefore raising perspectives for ex vivo gene therapy in early stages of liver diseases; 70 (iii) repeated hepatocyte infusions (fresh and/or cryopreserved hepatocytes) allowed to obtain metabolic benefits; 70,72 and (iv) hepatocyte transplantations were insufficient to fully correct the metabolic liver diseases, therefore re-emphasizing the limitations of hepatocyte transplantation, in particular the inefficient repopulation of the recipient liver by donor cells. 1,74,75 Understanding the transplantation mechanisms, engraftment and repopulating ability of transplanted hepatocytes is therefore critical for defining suitable strategies to increase the transplanted hepatocyte mass.…”
Section: Hepatocyte Transplantation In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…70,72,73 These studies also showed that: (i) transplantation of normal hepatocytes as few as 1% of the patient liver mass could lead to metabolic benefits; 73 (ii) hepatocyte transplantation was safe in babies, therefore raising perspectives for ex vivo gene therapy in early stages of liver diseases; 70 (iii) repeated hepatocyte infusions (fresh and/or cryopreserved hepatocytes) allowed to obtain metabolic benefits; 70,72 and (iv) hepatocyte transplantations were insufficient to fully correct the metabolic liver diseases, therefore re-emphasizing the limitations of hepatocyte transplantation, in particular the inefficient repopulation of the recipient liver by donor cells. 1,74,75 Understanding the transplantation mechanisms, engraftment and repopulating ability of transplanted hepatocytes is therefore critical for defining suitable strategies to increase the transplanted hepatocyte mass.…”
Section: Hepatocyte Transplantation In Humansmentioning
confidence: 99%
“…77,79,80 Subsequently, translocated cells integrated into the liver parenchyma, regained their polarity with the formation of gap junctions and bile canaliculi between transplanted and host hepatocytes within about 1 week, without any significant proliferation in adult animals and were functional throughout the life of animals. 74,75,81 Overall, only 20-30% of transplanted hepatocytes integrated into the liver. For instance, transplantation of 2 Â 10 7 hepatocytes led to the repopulation of about 0.5% of the host liver by transplanted cells.…”
Section: Hepatocyte Transplantation Mechanismsmentioning
confidence: 99%
“…20-HETE affects movement of ions, constricts blood vessels, is involved in renal autoregulation and tubuloglomerular feedback, and is mitogenic. 5,6 It is a major factor elevating blood pressure in the spontaneously hypertensive rat. 7 20-HETE is predominantly formed in preglomerular arteries and arterioles but is also produced in the renal…”
Section: Commentsmentioning
confidence: 99%
“…5 Work by others showed that although transplanted hepatocytes integrated in the liver parenchyma, cells did not proliferate significantly in the normal liver. 6,7 In contrast, Overturf et al found that normal hepatocytes underwent extensive proliferation in the liver of FAH ᭝exon5 mice that were not treated with NTBC. 5 An interesting finding was that genetically corrected mutant hepatocytes were also positively selected with restoration of the liver to normal.…”
mentioning
confidence: 95%
See 1 more Smart Citation